Infrastructure Investments in Developing Economies – The case of Vietnam - Dang, Giang; Low, S. (Springer, 2014)
This book aims to provide knowledge on how infrastructure is planned and built in a typical developing country, and what key variables are there in the system limiting the efficient use of public investments in infrastructure. The book begins with a comprehensive literature review on construction and economic development, and trade and economic development. The focus of the book is on the case of Vietnam, with lessons drawn for other developing economies. The book employs the mixed use of data to provide a stronger basis for analysis and interpretation of related government policies. Based on the research findings, the book recommends significant capacity building work for Vietnam to develop capacities that would remove constraints on the efficient use of public investments in infrastructure. The general principles of significant capacity building work which are useful for policy implications are introduced in the book. Analysts, academics, public and private communities in developing countries can adopt the research findings as guiding principles to bring about changes in their current use of public investments in infrastructure, thus supporting their trade and economic growth in the long term.